Reproducibility of Naked Eye Single Tube Red cell Osmotic Fragility Test (NESTROFT) as a screening test for the detection of b thalassemia and Hemoglobin E traits with the variation of reading time - Karim, Md Anwarul; Jamal, Chowdhury Yakub; Mia, MA Mannan (Bangladesh Journal of Child Health, 2024)
Background: Though 0.36% NaCl buffered solution has been used as an effective reagent for carrying out Naked Eye Single Tube Red cell Osmotic Fragility Test (NESTROFT) as a screening test for the detection of b thalassemia and Hemoglobin E traits, reading time for its interpretation is yet to be settled. Methods: This cross -sectional analytic study was done at Department of Pediatric Hematology and Oncology, BSMMU from January 2006-June 2007. NESTROFT was performed in 3 separate tubes for each of the 100 subjects (with â thalassemia trait and HbE trait and normal hemoglobin) with 0.36% NaCl buffered solution and reading was taken at different time at 5-minute, 15-minuteand 30-minute. Results were recorded as positive and negative. Hb electrophoresis, Hemogram with RBC indices for each sample and iron profile of selected subjects were done. Results: Among the 100 study subjects, 48 were carriers (18 were â thalassemia traits, 30 were Hb E traits). Age range was 1 to 52 yrs. Mean Hemoglobin concentration, MCV, MCH of both b thalassemia and Hb E carrier were significantly lower than normal subjects (p values <. 001). At 5-minute observation, NESTROFT was positive in 17 out of 18 â thalassemia traits with a sensitivity of 94.4%, 24 out of 30 HbE traits gave positive result with a sensitivity of 80%. Among the 52 normal subjects 35 gave negative result with a specificity of 67%. Positive predictive value and negative predictive value for detection of b thalassemia traits and HbE traits were 50% & 97% and 58% and 85%respectively. Result of NESTROFT interpreted at 15-minute and 30-minute did not show any change. Conclusion: From this study it may be concluded that for interpretation of NESTROFT reading at 5-minute would be optimum. BANGLADESH J CHILD HEALTH 2022; VOL 46 (3) : 130-137